TechnoServe in Ghana - World Bank (Washington, DC, 2012)
TechnoServe (TNS) is an international non-governmental organization founded in 1968 and has programs in 14 countries in Africa, Latin America and Central Europe. The Ghana program was established in 1971. TechnoServe's mission is to establish sustainable community-based enterprises that increase productivity, income and employment. It opposes food relief, subsidized inputs and grants and promotes self-help and technical assistance to rural communities. This approach involves the provision of financial and business management training in order to help these communities make sound business decisions and create and operate their own enterprises. Although TNS believed that the key to financing these small community-based enterprises was savings, eventually it became convinced that credit was also necessary. TNS therefore evolved its own financial mediation strategy by developing innovative mechanisms for micro-enterprise financing.